Enhancement of polyamide laser sinter powder reusability by acid catalyzed hydrolysis - Hesse, Nicolas; Peukert, Wolfgang; Schmidt, Jochen (Procedia CIRP, 2020)
This contribution introduces a method to reverse the deterioration in melt rheological behaviour (‘ageing’) of polyamide 12 that has previously been used in powder bed fusion processing by reduction of the polymers molecular weight via acid catalysed hydrolysis. Chosen hydrolysis conditions allow for a reconditioning below melting temperature and therefore leave the particulate nature of the powder intact while significantly improving the polymers rheological properties. The influences of different temperatures, acids and pH-values are investigated and the processability of recycled powders is assessed by melt rheological, optical and thermal characteristics.
Keywords: powder bed fusion; selective laser sintering; polyamide 12; powder reusability; hydrolysis; molecular chain length; zero shear viscosity